Model predictive control: a review of its applications in power electronics - Vazquez, Sergio; León, José; Franquelo, Leopoldo; Rodriguez, Jose; Young, Hector A.; Marquez, Abraham; Zanchetta, Pericle (Institute of Electrical and Electronics Engineers, 2014)
Model-based predictive control (MPC) for power converters and drives is a control technique that has gained attention in the research community. The main reason for this is that although MPC presents high computational burden, it can easily handle multivariable case and system constraints and nonlinearities in a very intuitive way. Taking advantage of that, MPC has been successfully used for different applications such as an active front end (AFE), power converters connected to resistor inductor RL loads, uninterruptible power supplies, and high-performance drives for induction machines, among others. This article provides a review of the application of MPC in the power electronics area.